Doing different things or doing things different: exploring the role of action learning in innovation. (2nd January 2016) - Abbott, Christine; Weiss, Michael
ABSTRACT: The notion of action learning driven innovation is explored with reference to three action-learning projects carried out in the last year and a proposed multi stakeholder project starting in 2016. The authors also provide an account of 'innovation', including its rationale and characteristics, and argues for its particular suitability in the practice of action learning.